Relationships between body weight and percentage body fat in the body and the development of osteopenia and osteoporosis - Dariusz Wolski; Jerzy Bednarski; Iwona Łuszczewska-Sierakowska; Joanna Michalik; Agata Wawrzyniak; Grzegorz Nowicki; Anna Bodajko-Grochowska; Jakub Kosiński (Kazimierz Wielki University, 2018)
Obesity nowadays is a significant problem in developing countries and developed ones. Both the percentage of adipose tissue in the body and the proportion of muscle tissue affect the condition of the skeletal system. The common origin of adipose tissue and muscle tissue shows that overweight and obesity are not indifferent to the metabolism of bone tissue. Both malnutrition and obesity can lead to unfavorable health effects, contributing to the development of bone disorders and the occurrence of osteopenia, osteopenia with sarcoidosis, osteoporosis or osteoarthritis. Increased percentage of adipose tissue and/or muscle tissue during menopause may have an osteoprotective effect and thus prevent or relieve the effects of menopause in women or andropause in men. Research aimed at measuring the content of adipose tissue as a supplement to other diagnostic tests may contribute to the early detection and even prevention of osteoporosis. Key words: BMI, obesity, osteoporosis, osteopenia